Photochromism and photomagnetism in three cyano-bridged 3d–4f heterobimetallic viologen frameworks. Issue 14 (25th March 2021) - Li, Meng-Hua; You, Ming-Hua; Lin, Mei-Jin
Abstract : Three 3-D isostructural cyanide-bridged 3d–4f heterobimetallic complexes with enhanced photochromism and photomagnetism at RT have been achieved by the introduction of a photoactive viologen functionalized ligand. Abstract : The incorporation of photochromic moieties into coordination polymers is of particular interest because it can endow them with various switching functions such as electrical conductivity, luminescence, and magnetism. In this context, a viologen ligand as a photochromic moiety was incorporated into 3d–4f heterobimetallic hexacyanoferrates, resulting in three novel 3-D photochromic complexes with different metal cations, namely [Ln(BCEbpy) M(CN)6 (H2 O)4 ]·2H2 O n (denoted as CoDy, CoEu, and FeDy, Ln = Dy, Eu; M = Fe, Co, H2 BCEbpy·2Br = N, N ′-bis(carboxymethyl)-4, 4′-bipyridinium dibromide). And the photoresponsive mechanism has been well discussed based on the solid UV-vis, IR, ESR, photoluminescence, and magnetism data. Moreover, accompanying the photochromic process, these unique complexes exhibit different photomagnetic behaviors upon UV-vis irradiation at RT because of the different ferromagnetic coupling interactions between photogenerated radicals and lanthanide cations.